MULTIFUNCTIONALITY OF RADIO RECEIVING DEVICES (Western European Journal of Modern Experiments and Scientific Methods, 2025)
The article presents radio receiving devices that are designed to receive radio signals and convert them to a form that allows the use of the useful information contained in them.